Femtosecond Stimulated Raman Study of Excited-State Evolution in Bacteriorhodopsin - McCamant, David W. (2005)
Femtosecond time-resolved stimulated Raman spectroscopy (FSRS) is used to examine the photoisomerization dynamics in the excited state of bacteriorhodopsin. Near-IR stimulated emission is observed in the FSRS probe window that decays with a 400–600-fs time constant. Additionally, dispersive vibrational lines appear at the locations of the ground-state vibrational frequencies and decay with a 260-fs time constant. The dispersive line shapes are caused by a nonlinear effect we term Raman initiated by nonlinear emission (RINE) that generates vibrational coherence on the ground-state surface. Theoretical expressions for the RINE line shapes are developed and used to fit the spectral and temporal evolution of the spectra. The rapid 260-fs decay of the RINE peak intensity, compared to the slower evolution of the stimulated emission, indicates that the excited-state population moves in ∼260 fs to a region on the potential energy surface where the RINE signal is attenuated. This loss of RINE signal is best explained by structural evolution of the excited-state population along multiple low-frequency modes that carry the molecule out of the harmonic photochemically inactive Franck–Condon region and into the photochemically active geometry.